Environmental Analyses to Inform Transitions to Sustainable Diets in Developing Countries: a Component of the EATS Project - Heller, Martin C.; Walchale, Abhijeet; Heard, Brent R.; Hoey, Lesli; Khoury, Colin K.; Haan, Stef de; Burra, Dharani Dhar; Thi, Thanh Duong; Osiemo, Jamleck; Jones, Andrew D. (International Conference on Green and Sustainable Innovation (ICGSI), 2018)
Sustainable diets are an environmental, economic and public health imperative, but identifying clear intervention points is challenging. The Entry points to Advance Transitions towards Sustainable diets (EATS) project seeks to repackage existing data, combined with an interview-informed awareness of current national and sub-national policy processes, to inform food system-level decision making. Here we view historic trends in food supply in Vietnam and Kenya as a proxy for national average diets, and consider them in terms of the greenhouse gas emissions and cumulative energy demand associated with producing that food. Economic prosperity in Vietnam in recent decades has led to increases in meat consumption and, in turn, amplified increases in diet level environmental impacts. Mild levels of beef consumption in Vietnam have now overcome the most popular meat, pork, as the dominant source of greenhouse gas emissions. Meanwhile, historically consistent levels of dairy and beef in Kenya dominate diet-level environmental impacts. This preliminary work will be integrated into later stages of the EATS project to promote systemic approaches to sustainable development.